Technological Advancements in the Prevention, Diagnosis, and Management of Heart Disease: A Theoretical Framework (The Science Post, 2025)
Heart disease continues to be the leading cause of mortality worldwide, presenting significantchallenges to healthcare systems, especially in aging populations and those with sedentarylifestyles. Technological innovation has introduced powerful tools that are transforming howcardiovascular diseases are prevented, diagnosed, and managed. This paper presents a theoreticalframework that integrates systems theory, socio-technical theory, and the Health Belief Model toevaluate how emerging technologies contribute to the evolving landscape of heart disease care. Byaligning theory with innovation, we explore the potential of technology to enhance patientoutcomes, clinical efficiency, and long-term disease prevention strategies.